Male depression syndrome is characterized by pronounced Cluster B personality traits - Sedlinská, Terezie; Mühle, Christiane; Richter-Schmidinger, Tanja; Weinland, Christian; Kornhuber, Johannes; Lenz, Bernd (Journal of affective disorders, 2021)
Background - Male depression syndrome (Male-DS) refers to alternative depression symptoms related to the male sex, such as externalizing behaviors, emotional suppression, substance misuse, and risk-seeking. Although these symptoms contribute to gender bias in the diagnosis of depression, Male-DS can be found in both sexes. In this cross-sectional study, we analyzed associations between Male-DS and clinical personality accentuations. - Methods - We compared clinical personality accentuations between 78 depressed patients with high Male-DS scores (46% women; mean age ± standard error of the mean: 36.5 ± 1.6 years) and 76 depressed patients with low Male-DS scores (43% women; age 44.8 ± 1.7 years). We also explored differences between the two patient groups and 176 healthy controls (51% women; age 37.2 ± 1.0 years). - Results - Depressed patients with high Male-DS scores showed stronger borderline (partial η2 0.121), impulsive (0.112), and antisocial (0.078) personality accentuations than those with low Male-DS scores after Bonferroni adjustment and controlling for sex, depression severity, and age. Relative to healthy controls, patients with high Male-DS values scored higher in all personality dimensions except for the narcissistic dimension. Patients with low Male-DS values scored higher in all Cluster A and C dimensions and the impulsive and borderline dimensions, but their scores were lower in the narcissistic dimension. - Limitations - Cross-sectional design and focus on in-patients. - Conclusions - We found pronounced Cluster B personality in patients with high Male-DS scores versus patients with low scores. Further prospective research is needed to verify that Cluster B personality traits represent a pre-morbid risk factor for Male-DS.
Gesehen am 01.02.2023